IMPROVING THE PERFORMANCE OF THE COPPER SULFIDE (CUS) NEGATIVE ELECTRODE WITH THE ADDITION OF NICKEL DOPAN IN ASYMMETRIC SUPERCAPACITORS - Roni Rodiansyah, Darul
The transition to clean energy using natural energy sources encounters obstacles due to their intermittent nature, while the increasing demand for energy necessitates the use of energy storage devices with large capacities capable of supplying and delivering substantial power in a short period of time. Supercapacitors emerge as a viable option due to their high power density, extensive number of charge and discharge cycles, and consequently longer operational lifespan compared to batteries. One type of supercapacitor with high energy density is the asymmetric supercapacitor (ASC). However, several ASCs are still not optimal because their negative electrodes exhibit lower performance compared to the positive electrodes. One potential candidate material for developing negative electrodes is copper sulfide (CuS), due to its good chemical stability, high electronic conductivity, low cost, abundant availability, and high theoretical capacitance. Nevertheless, monometallic TMS such as CuS face challenges related to weak structural stability, low intrinsic electrical conductivity, and lower capacity. Therefore, the performance of CuS still needs to be improved. Current synthesis methods for CuS also require a relatively long time, indicating the need for more effective synthesis methods that can also be used to synthesize other materials for a single supercapacitor cell. In this study, we synthesized CuS using a hot-injection method with a more effective timeframe. Ni doping on CuS using the same method was also conducted to enhance the performance of the resulting negative electrode. During the synthesis process, we varied the amount of Ni (0n%, 10n%, 20n%, 30n%) added to the CuS (CuS:Ni), obtaining the highest capacitance value with 20n% Ni doping. Based on electrochemical characterization, the capacitance of CuS increased from 367.40 F/g to 906.84 F/g at 1 A/g after adding 20n% Ni dopant. Characterization through CV and GCD revealed that this electrode behaves as a battery-like pseudocapacitor, with the charge storage mechanism predominantly governed by diffusion-controlled faradaic reactions. XRD characterization confirmed that the material formed was CuS with a hexagonal covellite structure and space group P63/mmc (#194). The XRD results for CuS:Ni 20n% showed the same diffraction peaks, but with a slight shift towards higher 2? angles, indicating smaller interatomic distances due to the presence of Ni. This finding was corroborated by SEM characterization, which showed that the particle size of CuS:Ni 20n% was smaller compared to CuS. The morphology of both samples was microflower-like, consisting of interlocking nanoflakes. Supported by BET surface characterization, both materials exhibited closed-ended pores, shaped like tubes or cones, similar to the gaps between nanoflakes. The pore size of CuS:Ni 20n% was smaller than that of CuS, reinforcing the mechanism whereby charge storage is dominated by diffusion-controlled faradaic reactions, with Ni enriching the occurring reactions. Subsequently, the negative electrodes of CuS and CuS:Ni 20n% were each assembled into an ASC using NiS as the positive electrode, synthesized through a similar method. The negative electrode of CuS 20n% consistently demonstrated higher performance compared to CuS. Results from the ASC NiS//CuS:Ni 20n% showed an energy density of 61.97 Wh/kg at a power density of 517.85 W/kg. Thus, the ASC NiS//CuS:Ni 20n% is competitive with other high-performance ASCs, particularly among CuS-based supercapacitors, and the high performance of the individual CuS:Ni 20n% negative electrode suggests its potential use in ASCs with other positive electrodes.